2018
DOI: 10.1101/261438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reversing Glial Scar Back To Neural Tissue Through NeuroD1-Mediated Astrocyte-To-Neuron Conversion

Abstract: Nerve injury often causes neuronal loss and glial proliferation, disrupting the delicate balance between neurons and glial cells in the brain. Recently, we have developed an innovative technology to convert internal reactive glial cells into functional neurons inside the mouse brain. Here, we further demonstrate that such glia-to-neuron conversion can rebalance neuron-glia ratio and reverse glial scar back to neural tissue.Specifically, using a severe stab injury model in the mouse cortex, we demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 52 publications
(69 reference statements)
7
21
0
Order By: Relevance
“…1C). Interestingly, like that reported in rodent models (Chen et al, 2019; Zhang et al, 2018), we found that some NeuroD1-GFP infected cells were immunopositive for both GFAP (red) and NeuN (blue) (Fig. 1D), suggesting a transitional stage in-between astrocytes and neurons during the conversion process.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…1C). Interestingly, like that reported in rodent models (Chen et al, 2019; Zhang et al, 2018), we found that some NeuroD1-GFP infected cells were immunopositive for both GFAP (red) and NeuN (blue) (Fig. 1D), suggesting a transitional stage in-between astrocytes and neurons during the conversion process.…”
Section: Resultssupporting
confidence: 86%
“…It appears that both NeuN+/GFAP+ double positive cells and NeuN-/GFAP-double negative cells were transitional cells during AtN conversion process. These results suggest that overexpression of NeuroD1 in the astrocytes of monkey brains can convert them into neurons, similar to that found in the mouse brains (Chen et al, 2019; Guo et al, 2014; Zhang et al, 2018).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Our group has previously demonstrated that the neurogenic transcription factor NeuroD1 can reprogram reactive astrocytes into functional neurons in the stab-injured brain and in a mouse model for Alzheimer's disease (Guo et al, 2014). Following studies demonstrated that NeuroD1-mediated in vivo astrocyte-to-neuron conversion can reverse glial scar back to neural tissue (Zhang et al, 2018) and repair the damaged motor cortex after ischemic stroke . The major goal of the current study is to determine whether NeuroD1 can reprogram reactive astrocytes into functional neurons in the injured spinal cord.…”
Section: Introductionmentioning
confidence: 99%